2022
DOI: 10.1186/s12884-022-04426-3
|View full text |Cite
|
Sign up to set email alerts
|

“This is hard to cope with”: the lived experience and coping strategies adopted amongst Australian women with pelvic girdle pain in pregnancy

Abstract: Background Women with pregnancy-related pelvic girdle pain (PPGP) report diminished ability to perform physical activities and experience higher rates of mood disorders, such as anxiety and depression, than pregnant women without PPGP. Despite these physical and psychological impacts, little is known about the lived experiences of PPGP amongst Australian women and the ways in which they cope. Situated within biographical disruption and social support theories, this study sought to gain a concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…The high prevalence of PPGP reported worldwide, coupled with the reported gaps in healthcare services offered to these women, signify a condition that requires improved caring solutions (Ceprnja et al, 2022; Fishburn & Cooper, 2015). Indeed, recent evidence reveals a significant proportion of women with PPGP may develop persistent pain which leads to a long‐term burden of disease if not managed effectively during pregnancy (Bergström et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high prevalence of PPGP reported worldwide, coupled with the reported gaps in healthcare services offered to these women, signify a condition that requires improved caring solutions (Ceprnja et al, 2022; Fishburn & Cooper, 2015). Indeed, recent evidence reveals a significant proportion of women with PPGP may develop persistent pain which leads to a long‐term burden of disease if not managed effectively during pregnancy (Bergström et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Information and communication technologies (ICT) including applications and websites, were described by women in this study as resources that might be able to promote S-C. Women's experiences with ICT during pregnancy are generally positive, with many reporting frequent use to search for information and provision of support for healthy behaviours (van den Heuvel et al, 2018). Women spoke of a need for information from trusted and credible sources to make informed choices about their care--a recurring theme in studies of women with PPGP (Ceprnja et al, 2022;Mackenzie et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents experiencing unexpected moderate to severe pain described how they felt despondent and inadequate, identi ed under the "care drivers" theme. The attitude of normal expectation of LBP, PGP or LPGP from antenatal providers and pregnant women, is a common revelation (18,39,42,44) and barrier in seeking out care. Women have reported not wanting to feel bothersome reporting pain or feel judged in their di culty coping with pain (42).…”
Section: Discussionmentioning
confidence: 99%
“…The attitude of normal expectation of LBP, PGP or LPGP from antenatal providers and pregnant women, is a common revelation (18,39,42,44) and barrier in seeking out care. Women have reported not wanting to feel bothersome reporting pain or feel judged in their di culty coping with pain (42). When they received prenatal advice on LPGP, respondents indicated that antenatal reassurance, exercise, relaxation, medication, and ergonomic advice did not improve disabling LPGP, nor improve sleep quality, ability to walk and pain hindered their exercise.…”
Section: Discussionmentioning
confidence: 99%